Measuring the quality of life in hypertension according to Item Response Theory - José Wicto Pereira Borges; Thereza Maria Magalhães Moreira; Jeovani Schmitt; Dalton Francisco de Andrade; Pedro Alberto Barbetta; Ana Célia Caetano de Souza; Daniele Braz da Silva Lima; Irialda Saboia Carvalho
ABSTRACT OBJECTIVE To analyze the Miniquestionário de Qualidade de Vida em Hipertensão Arterial (MINICHAL - Mini-questionnaire of Quality of Life in Hypertension) using the Item Response Theory. METHODS This is an analytical study conducted with 712 persons with hypertension treated in thirteen primary health care units of Fortaleza, State of Ceará, Brazil, in 2015. The steps of the analysis by the Item Response Theory were: evaluation of dimensionality, estimation of parameters of items, and construction of scale. The study of dimensionality was carried out on the polychoric correlation matrix and confirmatory factor analysis. To estimate the item parameters, we used the Gradual Response Model of Samejima. The analyses were conducted using the free software R with the aid of psych and mirt. RESULTS The analysis has allowed the visualization of item parameters and their individual contributions in the measurement of the latent trait, generating more information and allowing the construction of a scale with an interpretative model that demonstrates the evolution of the worsening of the quality of life in five levels. Regarding the item parameters, the items related to the somatic state have had a good performance, as they have presented better power to discriminate individuals with worse quality of life. The items related to mental state have been those which contributed with less psychometric data in the MINICHAL. CONCLUSIONS We conclude that the instrument is suitable for the identification of the worsening of the quality of life in hypertension. The analysis of the MINICHAL using the Item Response Theory has allowed us to identify new sides of this instrument that have not yet been addressed in previous studies.